2019
DOI: 10.1186/s13195-019-0549-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Aβ42/40 ratio alone or combined with FDG-PET can accurately predict amyloid-PET positivity: a cross-sectional analysis from the AB255 Study

Abstract: Background: To facilitate population screening and clinical trials of disease-modifying therapies for Alzheimer's disease, supportive biomarker information is necessary. This study was aimed to investigate the association of plasma amyloid-beta (Aβ) levels with the presence of pathological accumulation of Aβ in the brain measured by amyloid-PET. Both plasma Aβ42/40 ratio alone or combined with an FDG-PET-based biomarker of neurodegeneration were assessed as potential AD biomarkers. Methods: We included 39 cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 59 publications
6
44
0
Order By: Relevance
“…Compared to healthy controls, plasma Aβ42/Aβ40 was signi cantly decreased in AD patients and was in line with most previous studies, which showed a higher degree of consistency than single Aβ peptide even using different detection methods [7,25]. Decreased Aβ42/Aβ40 levels demonstrated value in re ecting pathological changes of AD and predicting cerebral Aβ status, whether regarding amyloid PET or CSF Aβ as a positive reference [26][27][28].…”
Section: Discussionsupporting
confidence: 89%
“…Compared to healthy controls, plasma Aβ42/Aβ40 was signi cantly decreased in AD patients and was in line with most previous studies, which showed a higher degree of consistency than single Aβ peptide even using different detection methods [7,25]. Decreased Aβ42/Aβ40 levels demonstrated value in re ecting pathological changes of AD and predicting cerebral Aβ status, whether regarding amyloid PET or CSF Aβ as a positive reference [26][27][28].…”
Section: Discussionsupporting
confidence: 89%
“…In two of the four studies sensitivity, specificity and AUC of plasma A␤ 42/40 for A␤-positive PET were more promising [28,47] compared with our own analysis comparing AD patients with controls. Yet, in one of these studies, when the full cohort was analyzed rather than a subsample, plasma A␤ 42/40 performed poorly in discriminating MCI from cognitively normal individuals [47], mirroring our own results. A cross-sectional analysis of people with subjective cognitive decline, too, found low AUC and low specificity of the compound alone for A␤-positive PET [48].…”
Section: Discussionmentioning
confidence: 73%
“…Further, a lower plasma A␤ 42/40 was reported in patients with mild cognitive impairment (MCI) compared with cognitively normal individuals; additionally MCI patients with lower plasma A␤ 42/40 were at increased risk of 2-year conversion to AD [45]. In two of the four studies sensitivity, specificity and AUC of plasma A␤ 42/40 for A␤-positive PET were more promising [28,47] compared with our own analysis comparing AD patients with controls. Yet, in one of these studies, when the full cohort was analyzed rather than a subsample, plasma A␤ 42/40 performed poorly in discriminating MCI from cognitively normal individuals [47], mirroring our own results.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations